Procedural Pain Assessment in Infants Without Analgosedation: Comparison of Newborn Infant Parasympathetic Evaluation and Skin Conductance Activity - A Pilot Study - Walas, Wojciech; Halaba, Zenon P.; Szczapa, Tomasz; Latka-Grot, Julita; Maroszyńska, Iwona; Malinowska, Ewelina; Rutkowska, Magdalena; Kubiaczyk, Agata; Wrońska, Monika; Skrzypek, Michał; De Jonckheere, Julien; Jean-Noel, Mickael; et al. (Frontiers in Pediatrics, 2022)
Objective: New technologies to measure pain responses, such as heart rate variability and skin conductance hold promise in the development of tools that can be reliable and quantifiable of detecting pain. The main objective of this study was to assess the capability of two monitors i.e., Newborn Infant Parasympathetic Evaluation (NIPE) and Skin Conductance Algesimeter for detecting procedural pain in non-anesthetized infants. Materials and Methods: Thirty-three non-anesthetized infants were enrolled to the study. To detect pain caused by heel stick, NIPE, and Skin Conductance monitors and behavioral pain scales were used. Three minutes before and just after heel stick, pain was evaluated by behavioral scales, and simultaneously over the whole period by NIPE and SCA. Results: A statistically significant decrease of NIPE Index and an increase of SCA values were found after the HS procedure. There were no statistically significant differences between the decrease in NIPEi values and the increase in PPS values between subgroups based on pain assessment by behavioral-scale scores. Conclusion: Both NIPE and SCA can be useful for detection of procedural pain and may constitue an additional valuable tool for better handling of pain among patients treated in NICUs. More studies on larger groups of patients are needed.